Pendampingan Penerapan Metode Process Costing pada UMKM Home Industri Tempe Ibu Jum di Bandar Lampung - Ade Widiyanti; Agus Zahron Idris; Chara Pratami Tidespania Tubarad (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activity aims to assist the Ibu Jum Tempe Home Industry MSME in Bandar Lampung in implementing the process costing method as a more accurate, measurable, and efficient production cost calculation system. To date, MSMEs still use simple cost recording without a clear separation between raw material costs, labor, and factory overhead, so that product selling prices often do not reflect actual production costs. To address this problem, this activity was carried out through several stages, namely interviews to explore MSME needs and problems, production process observations, socialization regarding the importance of cost accounting systems, and direct training in the preparation and implementation of process costing. The results of the activity showed an increase in MSME owners' understanding of cost classification, unit cost calculations, and the preparation of production cost reports. After the process costing method was implemented, MSMEs were able to calculate costs more systematically and consistently, thus being able to determine more appropriate and competitive selling prices. In addition, the implementation of this method also contributed to increased cost management efficiency, transparency of financial information, and the managerial ability of business actors in making more appropriate decisions related to cost planning and control.